2019
DOI: 10.1039/c9gc02153a
|View full text |Cite
|
Sign up to set email alerts
|

Improving the performance of supported ionic liquid phase (SILP) catalysts for the ultra-low-temperature water–gas shift reaction using metal salt additives

Abstract: Addition of CuCl to supported ionic liquid phase (SILP) catalysts enhances the activity in the low temperature water–gas shift (WGS) reaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 52 publications
(67 reference statements)
1
13
0
Order By: Relevance
“…20 to 40 %. Such a value was close to the benchmark of -alumina used here and in previous studies [22][23] . This observation also holds for a broader temperature range between 120 and 140 °C (see Supporting Information Figure S8).…”
Section: Composition Screening Of Novel Monolithic Supportssupporting
confidence: 90%
See 2 more Smart Citations
“…20 to 40 %. Such a value was close to the benchmark of -alumina used here and in previous studies [22][23] . This observation also holds for a broader temperature range between 120 and 140 °C (see Supporting Information Figure S8).…”
Section: Composition Screening Of Novel Monolithic Supportssupporting
confidence: 90%
“…-Al 2 O 3 (Sasol Germany GmbH) were fractioned to 200-500 µm to be used as reference support to prepare the benchmark WGS SILP catalytic system. [22][23] For the screening of new extruded support materials, extrudates were prepared, crushed and sieved to the same particle fraction of 200-500 µm as the benchmark alumina particles. The ionic liquid 1butyl-2,3-dimethylimidazolium chloride ([C 4 C 1 C 1 Im]Cl, > 97 %) were purchased from Merck KgaA, dichloromethane (DCM, ≥ 99.9 %) from Sigma-Aldrich, and the ruthenium precursors RuCl 3 (99.9 %) and the dimer [Ru(CO) 3 Cl 2 ] 2 (> 98 %) from Best Chemicals and Alfa Aesar, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, a serious counter-indication to the application of the SILP materials for this purpose is the poor solubility of carbon monoxide in the ionic liquids. Wolf et al investigated the effect of the addition of metal chlorides incorporated into the Ru-SILP system on the catalytic activity for WGSR and found that the incorporation of CuCl into the SILP material considerably improved the catalytic activity, as evidenced by the increase in the conversion by 30% [83]. The SILP materials with an ionic liquid having properties characteristic of Brønsted acids have been employed in the process of fuel desulfurization.…”
Section: Supported Ionic Liquid Phase Catalysts (Silpcs)mentioning
confidence: 99%
“…Homogeneous WGS is carried out using different transition metal complexes (Rh, Ru), even under mild conditions, which are usually doped with organic bases to increase the turnover rate [5,6]. Supported ionic liquids (SILP), prepared via the immobilization of ionic liquids on the solid material, have also been used for WGS [7]. In addition, hydrogen can be produced through the use of organisms that use the biological WGS reaction as a means of obtaining energy to maintain their metabolic processes and grow [8].…”
Section: Introductionmentioning
confidence: 99%